2007
DOI: 10.1097/01.wco.0000280411.57836.aa
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of sialorrhoea in patients with Parkinson??s disease: best current evidence

Abstract: (1) Sialorrhoea is a common condition in patients with Parkinson's disease that has a negative impact on patient quality of life. (2) Traditionally, muscarinic antagonists have been the pharmacological agents of choice for the treatment of sialorrhoea; however, these agents are frequently associated with adverse events in patients with Parkinsonian disorders. (3) Recent studies suggest that botulinum toxin injection is currently the most effective treatment option for Parkinsonian-related sialorrhoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 27 publications
0
19
0
2
Order By: Relevance
“…Treatment with anticholinergics may be helpful, but they are frequently associated with side effects. 819 Botulinum toxin has emerged as the most effective treatment for sialorrhea in PD. Double-blind studies have demonstrated reduced drooling and reduced disability with both botulinum toxin A and B.…”
Section: Impulse Dyscontrol and Dopamine Dysregulation Disordersmentioning
confidence: 99%
“…Treatment with anticholinergics may be helpful, but they are frequently associated with side effects. 819 Botulinum toxin has emerged as the most effective treatment for sialorrhea in PD. Double-blind studies have demonstrated reduced drooling and reduced disability with both botulinum toxin A and B.…”
Section: Impulse Dyscontrol and Dopamine Dysregulation Disordersmentioning
confidence: 99%
“…Siyalore için yap›lan BT enjeksiyonlar›n›n yan etkileri aras›nda a¤r›, lokal hematom, tükürük kanal›nda tafl oluflumu, tükürük bezinde enfeksiyon, a¤›z kurulu¤u, disfaji ve çene kaslar›nda güçsüzlük say›labilir (48,49). Amiyotrofik lateral skleroz hastalar›nda BT uygulamas› yaparken özellikle disfaji ve çene kaslar›nda güçsüzlü¤ün ortaya ç›kabilme ihtimali göz önüne al›nmal›d›r.…”
Section: Siyaloreunclassified
“…Ce symptôme, à l'origine d'une morbidité psychosociale et physique, est retrouvé chez l'adulte dans les atteintes neurologiques telles que la sclérose latérale amyo-DOI de l'article original : 10 [4]). L'utilisation des anticholinergiques par voie systémique [2], l'atropine et la scopolamine, est efficace mais contreindiquée en cas de glaucome, d'uropathie obstructive et de myasthénie. Ces traitements disponibles sous forme de patchs de scopolamine ou de gouttes sublinguales d'atropine, sont d'efficacité reconnue mais limitée du fait des difficultés d'observance.…”
Section: Introductionunclassified